Factors Affecting the Successful Growth and Survival of Small and Micro Enterprises (SMEs) in Zimmerman Ward, Nairobi County a Kenya (Global Journal of Management and Business Research, 2017)
Small and micro- enterprises play an important role in developing a country even though they are not given adequate attention and have been biased towards larger and listed enterprises. This study investigates the factors affecting the successful growth and survival of small and micro- enterprises in Zimmerman ward, Nairobi County. The survey utilized a descriptive research design whereby descriptive statistics based on frequency tables and graphs provided information on demographic variables. Data was collected through questionnaire instrument. Convenience sampling technique was used because of the rationale that respondents were easily accessible. Statistical Package for Social Sciences 20.0 was used to analyze and present results. Techniques used included percentage analysis, samples and mean analysis. Inferential statistics (Pearson Product-Moment Correlation Coefficient) and multiple regressions were then applied to determine prediction level of the variables.
Keywords: criterion variable; contingency theory; motivation; performance; competence